What does mediated electrochemistry reveal about regional differences in the redox properties of Boom Clay?. (September 2020) - Hoving, Alwina L.; Sander, Michael; Frederickx, Lander; Dugulan, Achim Iulian; Bruggeman, Christophe; Behrends, Thilo
Abstract: The Boom Clay is a potential host rock for geological storage of radioactive waste in the Netherlands and Belgium. The redox properties of the host rock are important in the context of safety assessment as they affect the speciation and thus the mobility of redox sensitive radionuclides. In this study, redox properties of the clay were assessed by mediated electrochemical analyses. The electron donating (EDC) and accepting (EAC) capacities and reduction potential of a suite of Boom Clay samples were determined. Boom Clay samples from various locations in the Netherlands and Belgium were investigated in unaltered form, and after size separation or chemical treatment to relate variations in redox properties to regional differences in diagenetic history or in the assemblage of allogenic minerals. In the investigated samples, the EDC can be attributed to the oxidation of pyrite, Fe II in clay minerals and reduced natural organic matter (NOM) while the EAC can be ascribed to the reduction of Fe III in clay minerals and in Fe (oxyhydr)oxides. Combining Na-pyrophosphate extraction, to remove reactive NOM, with mediated electrochemical oxidation (MEO) allowed determining the individual EDC of NOM and Fe II in clay minerals. Mediated electrochemical analysis showed systematic differences between samples from two locations in the Netherlands, Zeeland and Limburg. In samples from Zeeland, the reduction potential was higher, the EAC was larger, and the contribution of NOM to the EDC was smaller compared to samples from Limburg. These differences can be attributed to partial oxidation of Boom Clay in Zeeland during its diagenetic history but partial oxidation could also be a storage artefact. The electron yield obtained by pyrite oxidation in samples from Zeeland was larger compared to those from Limburg, which can be explained by a smaller particle size of pyrite in Zeeland. The size of pyrite particles, in turn, can be used as a proxy for the depositional conditions. The electrochemical activity of Fe in clay minerals did not vary systematically between the two locations in the Netherlands. In general, the fraction of electrochemically active Fe in clay minerals increased with the relative content of 2:1 clay minerals. In comparison with samples from the Netherlands, larger fractions of structural Fe in clay minerals were redox-active in samples from Belgium, which had a higher chlorite or glauconite content. This study demonstrates that mediated electrochemical analysis can reveal redox properties of Boom Clay, which might be of relevance for the migration of redox sensitive radionuclides or when assessing the impact of constructing and operating a repository for nuclear waste on the surrounding host rock. Highlights: Regional differences in the redox properties of Boom Clay were detected by mediated electrochemical analysis. Redox activity of iron in clay minerals (Fe-clay) from Boom Clay increased with its content of 2:1 clay minerals. Larger fractions of Fe-clay were redox-active in samples from Belgium, which had a higher chlorite or glauconite content. Combining MEO with P2 O7 -extraction allowed to separate the contribution of Fe-clay and NOM to the EDC of clay sediments.